INOVASI PEMBERDAYAAN PRODUK UNGGULAN DAERAH: SINERGITAS DINAS, TEKNOLOGI TEPAT GUNA DAN MEDIA DIGITAL UNUTK UMKM BATIK BAKARAN - Diana Laily Fithri; Diah Ayu Susanti; Rochmad Winarso; Achmad Ridwan (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2025)
The community service activities for the superior products of Pati Regency in the second year have been going well by involving synergy between higher education institutions, the Cooperatives and MSMEs Office, and batik business partners. The program started with socialization and access to capital, followed by training in product photography and the provision of a mini studio that produced more attractive batik catalogs. Training in marketing management and website creation also helped partners utilize digital media as a promotional tool. In the implementation phase, appropriate technology (TTG) such as a marketing website, ergonomic colet tables, night boilers, and batik drying rooms successfully improved production efficiency and quality. In addition, management and financial mentoring strengthened the independence of partners in managing their businesses. The websites www.yuliatiwarno.com and www.misihbatik.com are now online showcases that expand market reach, while the product catalog from photography training supports more professional promotion. Overall, these activities can enhance the competitiveness, productivity, and sustainability of Batik Bakaran SMEs, as well as provide a strong foundation for future branding and marketing development. Abstrak Kegiatan pengabdian produk unggulan daerah Kabupaten Pati tahun kedua berjalan baik dengan melibatkan sinergi perguruan tinggi, Dinas Koperasi dan UMKM, serta mitra usaha batik. Program dimulai dari sosialisasi dan akses permodalan, dilanjutkan dengan pelatihan fotografi produk serta penyediaan mini studio yang menghasilkan katalog batik lebih menarik. Pelatihan manajemen pemasaran dan pembuatan website juga membantu mitra memanfaatkan media digital sebagai sarana promosi. Pada tahap penerapan, teknologi tepat guna (TTG) seperti website pemasaran, meja colet ergonomis, pelorot malam, dan ruang pengering batik berhasil meningkatkan efisiensi dan kualitas produksi. Selain itu, pendampingan manajemen dan keuangan memperkuat kemandirian mitra dalam mengelola usaha. Website www.yuliatiwarno.com dan www.misihbatik.com kini menjadi etalase online yang memperluas jangkauan pasar, sedangkan katalog produk dari pelatihan fotografi mendukung promosi secara lebih profesional. Secara keseluruhan, kegiatan ini dapat meningkatkan daya saing, produktivitas, dan keberlanjutan UMKM Batik Bakaran serta memberi dasar yang kuat untuk pengembangan branding dan pemasaran di masa depan.